A silicon dioxide-based composite material and its preparation method and application
By adopting a core-shell structure, the refractive index difference between zinc oxide and silica polymer is used to solve the problems of high transparency and insufficient hiding power in toothpaste, the effects of high hiding power and low transparency are achieved, and the market demand for white paste toothpaste is met.
Patent Information
- Application Number
- CN202410033003.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-01-09
AI Technical Summary
The silica prepared by traditional precipitation method cannot meet the market demand for white paste toothpaste in toothpaste because it has high transparency and insufficient hiding power.
A silica-based composite material with a core-shell structure is used. The core layer is zinc oxide and the shell layer is a silica polymer. It is prepared by a one-step precipitation method to control the amount of zinc oxide and the reaction conditions to obtain a material with high hiding power and low transparency.
The low transparency and high hiding power of the silica-based composite material in the toothpaste can be achieved, and white paste toothpaste can be prepared without adding additional whitening agent, which improves the whiteness and appearance quality of the product.
Smart Images

Figure CN118001167B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic materials, and in particular to a silicon dioxide-based composite material and a preparation method and application thereof. Background Art
[0002] Silica prepared by traditional precipitation method has stable physical and chemical properties and chemical inertness. When applied to toothpaste for oral cleaning, it will not affect the performance of the original system. And because it contains a large number of hydroxyl groups on its surface, it can form a hydrogen bond network system with itself and -OH / -NH / HF in the toothpaste system, thereby enhancing its bonding with the system. Therefore, this type of silica is often used as a thickener. In addition, the amorphous silica synthesized by precipitation method belongs to inorganic polymers. The compact structure of the silica matrix can be adjusted by adjusting the production parameters of the synthesis process to obtain silica with different friction properties, which can be applied to different toothpaste systems to increase the diversification of toothpaste and meet different needs on the market.
[0003] In recent years, the proportion of transparent toothpaste in the toothpaste market has been decreasing, and the demand for white toothpaste has been increasing. Silica prepared by precipitation method is the only abrasive for preparing transparent paste. The transparency of silicon powder is relatively high. When no other whitening agents are added to the toothpaste formula containing silica, the paste will appear transparent or translucent, affecting the appearance. Therefore, the application of silica in white paste is limited and cannot meet the current market demand for white toothpaste. In order to expand the application of silica in white paste, it is urgent to develop silica with high hiding power and low transparency to reduce the transparency of the silica-containing toothpaste system and improve the whiteness. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the object of the present invention is to provide a silicon dioxide-based composite material having a core-shell structure, wherein the core layer is zinc oxide and the shell layer is a silicon dioxide polymer, and the silicon dioxide-based composite material has high hiding power and low transparency.
[0005] The second aspect of the present invention is to provide a method for preparing a silicon dioxide-based composite material.
[0006] The third aspect of the present invention is to provide a toothpaste abrasive.
[0007] A fourth aspect of the present invention is to provide a toothpaste.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a silicon dioxide-based composite material, wherein the silicon dioxide-based composite material has a core-shell structure, wherein the core layer is zinc oxide and the shell layer is a silicon dioxide polymer;
[0010] The silica composite material D 50 Particle size <20μm.
[0011] It should be noted that the silica polymer refers to the silicate existing as an orthosilicic acid monomer in the aqueous solution state. Under the action of a catalyst (acid, base), the monomer will undergo SN2 nucleophilic substitution, and the two monomers will be linked by O-Si-O, and a water molecule will be removed to form a dimer. The dimer continues to condense to form a trimer, a tetramer, etc. The condensation continues to form silica oligomers and finally a silica polymer.
[0012] The present invention adopts an ideal core-shell structure to construct a new silica-based composite material, and successfully obtains a silica-based composite material with a core-shell structure. When the incident light in the external medium reaches the outer shell of the core-shell structure of the silica-based composite material, the first refracted light, scattered light, reflected light and other light will occur, and the first refracted light will be used as the incident light of the core-shell layer to generate the second refracted light, scattered light, reflected light and other light at the core-shell interface. Generally speaking, the greater the difference in the refractive index of the two media, the weaker the light intensity directly transmitted at the interface of the two media, the greater the intensity of reflection and scattering, and the greater the covering power embodied.
[0013] The core layer of the present invention is zinc oxide, whose refractive index is 2.008-2.029, while the refractive index of silicon dioxide is 1.435-1.460, so the refractive index of the core layer and the shell layer of the obtained silicon dioxide-based composite material is very different, that is, when the incident light enters the interface of the zinc oxide-silicon dioxide layer, due to the large difference in refractive index, the intensity of the reflected and scattered light is high, and the silicon dioxide-based composite material has high covering power. At the same time, because the present invention uses zinc oxide and silicon dioxide with a large difference in refractive index for compounding, and gives a specific core-shell structure, the obtained silicon dioxide-based composite material has the characteristics of low transparency.
[0014] The core-shell structure designed by the present invention adopts two interfaces, namely, the silicon dioxide-based composite material layer-external medium interface and the zinc oxide layer-silicon dioxide layer interface, and performs two reflection and scattering processes on the incident light from the medium. Among them, the strength of the covering power can be expressed by opacity, and the higher the covering power, the higher the opacity.
[0015] In some embodiments of the present invention, the maximum transparency of the silica-based composite material within the refractive index range of 1.330 to 1.460 is 15 to 50%.
[0016] In some embodiments of the present invention, the maximum transparency of the silica-based composite material within the refractive index range of 1.330 to 1.460 is 15 to 25%.
[0017] In some embodiments of the present invention, the maximum transparency of the silica-based composite material within the refractive index range of 1.330 to 1.460 is 17 to 20%.
[0018] In some embodiments of the present invention, the silica-based composite material has an oil absorption value (DOA) of 50 to 200 g / 100 g.
[0019] In some embodiments of the present invention, the silica-based composite material has an oil absorption value (DOA) of 70 to 100 g / 100 g.
[0020] In some examples of the present invention, the silica-based composite material has an oil absorption value (DOA) of 75 to 95 g / 100 g.
[0021] In some embodiments of the present invention, the water absorption capacity of the silica-based composite material is 10 to 40 ml / 20 ml.
[0022] In some embodiments of the present invention, the water absorption capacity of the silica-based composite material is 15 to 20 ml / 20 ml.
[0023] In some embodiments of the present invention, the volatile matter content of the silica-based composite material at 105° C. is 1 to 10%.
[0024] In some embodiments of the present invention, the volatile matter content of the silicon dioxide-based composite material at 105° C. is 2-5%.
[0025] In some examples of the present invention, the volatile matter content of the silica-based composite material at 105° C. is 2.3-4.8%.
[0026] A second aspect of the present invention provides a method for preparing a silicon dioxide-based composite material, comprising the following steps:
[0027] A zinc oxide-sulfate slurry containing 0.3-5% zinc oxide by mass is prepared, and silicate and an acidulant are added to react, and after aging, the silicon dioxide-based composite material is obtained.
[0028] The present invention adopts a one-step precipitation method, and zinc oxide is added to compound with silicate and an acidulant to generate silica, so that the prepared silica-based composite material has high hiding power and low transparency. The method uses silicate as a silicon source, adds an acidulant to react, acidifies the silicate, hydrolyzes to generate silica, and gradually polymerizes silica polymers on the surface of the exogenous additive zinc oxide, and then matures to obtain a silica-based composite material with low transparency and high hiding power.
[0029] Among them, the amount of zinc oxide has a key influence on whether the core-shell structure can be successfully obtained, and on improving the hiding power and reducing the transparency of the silica-based composite material. By adopting a one-step precipitation method and controlling the amount of zinc oxide, a silica-based composite material with high hiding power and low transparency can be obtained.
[0030] In some embodiments of the present invention, the silicate and the acidulant are added in the following manner: after adding the silicate to the zinc oxide-sulfate slurry, the silicate and the acidulant are added simultaneously, and then the acidulant is added continuously.
[0031] In some embodiments of the present invention, during the simultaneous addition of silicate and acidulant, the pH value of the system is controlled to be 8-10; and / or, after the acidulant is continued to be added, the pH value of the system is controlled to be 3-4.
[0032] In some specific embodiments of the present invention, during the process of adding the silicate and the acidulant simultaneously, the pH value of the system is controlled to be 8.4-9.6.
[0033] In some examples of the present invention, during the process of simultaneously adding the silicate and the acidulant, the pH value of the system is controlled to be 9.4-9.6.
[0034] In some embodiments of the present invention, the mass fraction of zinc oxide in the zinc oxide-sulfate slurry is 0.35-1.6%.
[0035] In some embodiments of the present invention, the mass fraction of zinc oxide in the zinc oxide-sulfate slurry is 0.5-1.5%.
[0036] In some specific embodiments of the present invention, the mass fraction of zinc oxide in the zinc oxide-sulfate slurry is 1.4-1.5%.
[0037] In some examples of the present invention, the mass fraction of zinc oxide in the zinc oxide-sulfate slurry is 0.35wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.7wt%, 1wt%, 1.4wt%, 1.45wt%, 1.5wt%, 1.6wt%, 2.5wt%, 3.5wt%, 4.5wt%, and 5wt%.
[0038] In some embodiments of the present invention, the silicate is an alkali metal silicate.
[0039] In some embodiments of the present invention, the alkali metal silicate is sodium silicate.
[0040] In some embodiments of the present invention, the silicate is added in the form of a silicate solution.
[0041] In some embodiments of the present invention, the concentration of the silicate solution is 0.1-2.0 mol / L.
[0042] In some embodiments of the present invention, the concentration of the silicate solution is 0.5-2.0 mol / L.
[0043] In some specific embodiments of the present invention, the concentration of the silicate solution is 1.5-2.0 mol / L.
[0044] In some examples of the present invention, the concentration of the silicate solution is 0.5 mol / L, 1 mol / L, 1.5 mol / L, or 2 mol / L.
[0045] In some embodiments of the present invention, the modulus of the silicate is 3 to 3.6.
[0046] In some embodiments of the present invention, the modulus of the silicate is 3 to 3.55.
[0047] In some embodiments of the present invention, the acidulant is a protonic acid or a strong acid and weak base salt.
[0048] In some embodiments of the present invention, the acidulant is one or more of sulfuric acid, hydrochloric acid, nitric acid, ammonium chloride and ferric sulfate.
[0049] In some embodiments of the present invention, the concentration of the acidifier is 1-4 mol / L.
[0050] In some embodiments of the present invention, the acidulant comprises at least one of hydrochloric acid and sulfuric acid.
[0051] In some embodiments of the present invention, the concentration of the acidifier is 2-4 mol / L.
[0052] In some examples of the present invention, the concentration of the acidifier is 3 to 3.5 mol / L.
[0053] In some embodiments of the invention, the sulfate is an alkali metal sulfate.
[0054] In some embodiments of the present invention, the sulfate is at least one of sodium sulfate and potassium sulfate.
[0055] In some embodiments of the present invention, the mass fraction of sulfate in the zinc oxide-sulfate slurry is 1-8%.
[0056] In some embodiments of the present invention, the mass fraction of sulfate in the zinc oxide-sulfate slurry is 3.5-7.5%.
[0057] In some examples of the present invention, the mass fraction of sulfate in the zinc oxide-sulfate slurry is 3%, 3.5%, 4%, 6%, 6.5%, 7%, 7.5%, or 8%.
[0058] In some embodiments of the present invention, the reaction temperature is 50-90°C.
[0059] In some embodiments of the present invention, the aging time is 0.5 to 1 hour.
[0060] In some embodiments of the present invention, the sulfate solution and zinc oxide are mixed by stirring for 0.5 to 1 hour.
[0061] In some embodiments of the present invention, the slurry is further subjected to filter pressing and washing after ripening, and then dried and crushed.
[0062] In some embodiments of the present invention, the drying method is air flow drying, with an inlet temperature of 300-350°C and an outlet temperature of 95-105°C.
[0063] In some embodiments of the present invention, the crushing is air flow crushing, the crushing pressure is 1 to 3 bar, and the rotating speed of the classifying wheel is 500 to 1500 rpm.
[0064] In some embodiments of the present invention, the method for preparing the silica-based composite material comprises the following steps:
[0065] S1. Adding a solid silicate having a modulus of 3 to 3.6 and process water to a liquefaction tank, and obtaining a concentrated silicate solution by high temperature and high pressure liquefaction;
[0066] S2. Add process water to the solution in step S1 and stir sufficiently to obtain a silicate solution having a concentration of 0.5 to 2 mol / L for standby use;
[0067] S3. The acid is configured into a 1-4 mol / L dilute acid solution as an acidifying agent to promote hydrolysis and set aside;
[0068] S4. preparing a sulfate solution with a mass fraction of 1 to 8 wt % for standby use;
[0069] S5. Add 0.3 to 5 wt% of ultrafine zinc oxide additive to the sulfate solution prepared in step S4, stir for 0.5 to 1 h, and set aside;
[0070] S6. Add 8-12m 3 The sulfate solution prepared in step S5 is controlled at a temperature of 50-90°C, and then 0.1-0.3 m silicate solution prepared in step S2 is added. 3 , stir evenly, and control the stirring frequency at 30-50Hz;
[0071] S7. Add the acidulant obtained in step S3 and the sodium silicate solution obtained in step S2 simultaneously for parallel neutralization reaction, and control the pH value of the process to be between 8 and 10; wherein the added volume of the silicate solution obtained in step S2 is 4.0 to 6.0 m 3 After the silicate is added, continue to drop the acidulant prepared in step S3 until the end point pH value reaches 3 to 4, stop dropping, continue stirring for 0.5 to 1 hour for maturation, and obtain a slurry;
[0072] S8. The slurry obtained after aging in step S7 is subjected to filter pressing and washing to obtain a silica filter cake, so that the conductivity of the washing water of the silica filter cake is less than 10000 us / cm, and then the obtained silica filter cake is air-dried with an inlet temperature of 300-350°C and an outlet temperature of 95-105°C, and then air-broken with a crushing pressure of 1-3 bar and a classifying wheel speed of 500-1500 rpm to obtain a silica-based composite material.
[0073] The second aspect of the present invention provides a method for preparing a silica-based composite material, using silicate as a silicon source and an acidic agent to react, and adding an exogenous additive zinc oxide, through a one-step precipitation method, while controlling the amount of zinc oxide, a layer of silica polymer is successfully polymerized on the surface of zinc oxide to obtain a silica-based composite material with high hiding power and low transparency. The D 50 The particle size is less than 20 μm, which is micron-sized.
[0074] Further controlling the process pH when the silicate reacts with the acidulant, the end point pH after the reaction, the amount of silicate used and the aging time can further improve the hiding power of the silica-based composite material. In addition, the silicon source selected in the above preparation method of the present invention is silicate, which has abundant raw material sources and has obvious advantages in large-scale production.
[0075] In some embodiments of the present invention, the silicate is sodium silicate, commonly known as water glass and sodium silicate, which is the most common silicon source.
[0076] The third aspect of the present invention provides a toothpaste abrasive, comprising the above-mentioned silica-based composite material, or the silica-based composite material obtained by the above-mentioned preparation method.
[0077] The silica-based composite material of the present invention and the silica-based composite material obtained by the preparation method have low transparency and high hiding power, and can be added to toothpaste as an abrasive to obtain a white paste without adding an additional whitening agent.
[0078] A fourth aspect of the present invention provides a toothpaste comprising the above-mentioned silica-based composite material, or the silica-based composite material obtained by the above-mentioned preparation method.
[0079] The silica-based composite material obtained by the present invention has low transparency and high hiding power, and can be used as an abrasive in toothpaste. In general toothpaste, moisturizers, sorbitol, glycerin, PEG400 and other solvents are mixed in a certain proportion, and their refractive index is between 1.330 and 1.460. The hiding power of the silica-based composite material obtained by the present invention essentially depends on the highest transparency of the silica-based composite material within the refractive index range of 1.330 to 1.460, and the highest point transparency of the silica-based composite material of the present invention does not exceed 50%, and the transparency is low. When used as an abrasive in toothpaste, a white paste can be successfully obtained.
[0080] In addition, zinc oxide has high biological activity and is an excellent antibacterial material. However, if the zinc oxide nanoparticles directly added in toothpaste can be transported into the brain through the tongue-brain pathway, it can induce neuroinflammation in the taste area of the cerebral cortex, thereby causing a decrease in neuronal synaptic transmission, which may lead to abnormal taste perception, which greatly increases the use risk of zinc oxide in daily necessities (toothpaste, mouthwash, food) and biomedicine. The core layer of the silicon dioxide-based composite material of the present invention is zinc oxide, which can slowly release a small amount of zinc ions when it is in an aqueous medium as a core, react with sulfhydryl, carboxyl, and hydroxyl groups in proteins in bacteria, destroy the internal structure of bacteria, and finally kill bacteria to achieve a sterilizing effect; and the shell silicon dioxide polymer is a high molecular inorganic polymer, and its microstructure can be regulated by controlling the preparation conditions in a one-step precipitation method preparation process, forming a dense structure, and the bioactive component zinc oxide can be coated, thereby playing the role of slow-release zinc oxide releasing zinc ions, and silicon dioxide belongs to a biologically inert material, has a mild chemical property, and has extremely high biosafety. These two materials were selected for core-shell composite, and the resulting silica-based composite material fully combines the high hiding power and excellent antibacterial properties of zinc oxide with the advantages of drug-loaded sustained-release and chemical inertness of silica, and has low transparency. While obtaining a white paste, it greatly improves the activity of zinc oxide in the oral cavity, increases the compatibility of zinc oxide with other active ingredients, and expands its application prospects.
[0081] In some embodiments of the present invention, the mass fraction of the silica-based composite material in the toothpaste is 8 to 25%.
[0082] In some embodiments of the present invention, the mass fraction of the silica-based composite material in the toothpaste is 15-20%.
[0083] In some embodiments of the present invention, the toothpaste comprises the following components by mass fraction: 8-25% silica-based composite material, 10-13% humectant, 55-63% sorbitol, 3-9% glycerol, 1-3% hydroxymethyl cellulose, 2-4% sodium lauryl sulfate, 0.1-0.3% saccharin sodium, 0.5-1% flavor, and 0.1-0.3% sodium benzoate.
[0084] In some embodiments of the present invention, the humectant comprises water.
[0085] Compared with the prior art, the present invention has the following beneficial effects:
[0086] (1) The silica-based composite material of the present invention has a core-shell structure, which can reflect and scatter external light twice. Due to the large difference in refractive index between the core layer and the shell layer, the intensity of reflected and scattered light at the core-shell interface is high, showing high hiding power, and the silica-based composite material obtained by combining zinc oxide with silica polymer has low transparency, and fully combines the antibacterial property of zinc oxide with the chemical inertness of silica, while improving the compatibility of the bioactive ingredient zinc oxide. Therefore, the silica-based composite material can be used as a new functional abrasive with antibacterial, anti-inflammatory and anti-allergic properties, enriching the choice of abrasive materials in the toothpaste field, and can increase the stability of the toothpaste system when used in the toothpaste system.
[0087] (2) The present invention adopts a one-step precipitation method, adds a specific amount of zinc oxide and the generated silicon dioxide for compounding, polymerizes a layer of silicon dioxide polymer on the surface of zinc oxide, and the obtained silicon dioxide-based composite material has high hiding power and low transparency, and further controls the reaction conditions such as pH, and can also regulate the microstructure of the silicon dioxide-based composite material to make the structure more compact, further improve the hiding power of the silicon dioxide-based composite material, and reduce the transparency, so that within the refractive index range of 1.330 to 1.460 (refractive index of the toothpaste liquid phase formula system), the transparency of the silicon dioxide-based composite material is lower, and an opaque paste appearance is prepared. At the same time, the preparation method adopted by the present invention is simple in process, does not require too much complicated operations, and has abundant raw material sources, and can achieve large-scale production.
[0088] (3) The silica-based composite material obtained by the present invention can be used as an abrasive in toothpaste. The obtained toothpaste is a white paste with excellent whiteness and a smooth appearance, which solves the problem that the traditional silica-containing toothpaste paste is transparent or translucent, saves the addition of color enhancers in the process of preparing white paste toothpaste, and avoids the risk of uneven mixing between the solid phase and the solid phase of the silica abrasive and the color enhancer during the toothpaste preparation process, thereby making up for the defect that silica cannot be used alone when preparing white paste in the oral field.
[0089] (4) The silica-based composite material obtained by the present invention has low transparency and high hiding power. It can be added in an amount of 8 to 25 wt% when preparing toothpaste, and no additional whitening agent needs to be added. This can make the toothpaste containing silica abrasive present a porcelain white and smooth appearance, thereby avoiding the problem that the white paste of the existing silica-containing toothpaste needs to be additionally added with a whitening agent during the preparation process, reducing the whitening agent addition process and reducing the production process management cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 This is a diagram of the synthesis mechanism of the silica-based composite material according to an embodiment of the present invention.
[0091] Figure 2 This is the SEM image of the silica-based composite material of Example 2. DETAILED DESCRIPTION
[0092] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0093] Some of the test methods for the following embodiments and comparative examples of the present invention are described as follows:
[0094] Water absorption: Weigh 20.0g of the sample (accurate to 0.01g) and place it in a dry enamel cup. Gradually drip 2-3mL of distilled water from the burette to allow the sample powder to absorb water evenly. Stir evenly with a tongue depressor, and keep dripping and shaking until all the sample powders become a ball. The water absorption is expressed as milliliters of distilled water consumed (unit: mL / 20g). The entire measurement process is required to not exceed 25min.
[0095] Oil absorption value: Weigh 1.0g to 2.0g (accurate to 0.0001g, recorded as M0) of silicon dioxide and place it on a glass plate, and add linseed oil drop by drop with a dropper; when dropping, use a tongue depressor to stir and tablet continuously, slow down the dropping speed before approaching the end point, stir and tablet thoroughly to avoid dropping beyond the end point; when the sample is pressed into a viscous, non-breakable and highly transparent sheet (the whole sheet will not fall apart after turning over), and there is no thickener and silicon dioxide powder left on the plate, read the consumed weight M of linseed oil. The calculation formula is as follows (oil absorption value unit g / 100g):
[0096] Oil absorption value X = (M0 / M) * 100
[0097] Volatile matter at 105℃: Weigh 2g of sample (accurate to 0.0001g) and place it in a weighing bottle with constant weight, weigh M1 and then place it in a 105℃ constant temperature oven for 2h, take it out and cool it to room temperature in a dryer, then weigh M2; the formula for calculating volatile matter at 105℃ is as follows:
[0098] X / %=(M1-M2) / 2*100%
[0099] Transparency at the highest point: (1) Preparation of a sorbitol / water mixture with a gradient refractive index: Prepare a stock solution of sorbitol and water according to a certain ratio: first weigh the required amount of sorbitol directly into a wide-mouthed bottle, then weigh the required amount of distilled water into the same wide-mouthed bottle, cover the bottle cap tightly, and shake vigorously to ensure that the solution is uniform; the refractive index of the sorbitol / water mixture must be between 1.330 and 1.464. If it is not reached, carefully adjust the sorbitol / water ratio to obtain the required refractive index; the refractive index can be determined by referring to the user manual of the Abela refractometer. (2) Preparation of test sample dispersion: Weigh 0.5±0.01g of silica-based composite material into each sterile bottle, add 12.0±0.01g of sorbitol / water mixture (different refractive index) into a centrifuge tube, cover the bottle cap and shake vigorously to make the silica-based composite material evenly dispersed in the sorbitol / water mixture, open the lid, place the bottle in a vacuum device, evacuate to vacuum with a vacuum pump, and maintain the vacuum for 1 hour; after 1 hour, slowly release the vacuum, take the sample out of the desiccator, and ensure that the air in the sample is completely removed by visual inspection, and immediately test and record the transparency (%) of the freshly prepared dispersion at 589nm to obtain the highest transparency.
[0100] Toothpaste appearance: Observe visually whether the toothpaste is transparent.
[0101] Example 1
[0102] This embodiment provides a method for preparing a silicon dioxide-based composite material, comprising the following steps:
[0103] S1. Add solid sodium silicate with a modulus of 3.45 to 3.55 and process water to a liquefaction tank, and obtain a concentrated sodium silicate solution by high temperature and high pressure liquefaction;
[0104] S2. Add process water to the solution in step S1 and stir sufficiently to obtain a sodium silicate solution having a concentration of 1.0 mol / L and set aside;
[0105] S3. The concentrated sulfuric acid is configured into a 3.0 mol / L dilute sulfuric acid solution for standby use;
[0106] S4. The sodium sulfate solution is configured to have a mass ratio of 3.5wt% sodium sulfate and set aside;
[0107] S5. Add 0.5wt% ultrafine zinc oxide additive to the sodium sulfate solution of step S4, stir for 30min, and set aside;
[0108] S6. Add 12m 3 The sodium sulfate solution prepared in step S5 is controlled at 75°C, and then 0.15 ml of the sodium silicate solution prepared in step S2 is added. 3 , stir evenly, and control the stirring frequency at 35Hz;
[0109] S7. Add the sodium silicate solution prepared in step S2 and the sulfuric acid solution prepared in step S3 simultaneously for parallel neutralization reaction, and control the pH value of the process at 8.5, wherein the added volume of the sodium silicate solution prepared in step S5 is 4.15m 3 After the sodium silicate is added, the dilute sulfuric acid solution prepared in step S3 is continued to be added dropwise until the end point pH value reaches 3.0 to 4.0, and then the addition is stopped and stirring is continued for 30 minutes for aging to obtain a slurry;
[0110] S8. The slurry after maturation in step S7 is subjected to filter pressing and washing to make the conductivity of the washing water of the silica filter cake less than 10000 us / cm, and then dried by air flow, with an inlet temperature of 320°C and an outlet temperature of 100°C, and then crushed by air flow with a crushing pressure of 1.4 bar and a classifying wheel speed of 1000 rpm to obtain a silica-based composite material, namely ZS-1.
[0111] The test showed that the silica-based composite material obtained in Example 1 had a water absorption of 19.2 ml / 20 ml, an oil absorption value (castor oil dry pressing) of 95 g / 100 g, 4.7% volatile matter at 105° C., and a maximum transparency of 20% within the refractive index range of 1.330 to 1.460.
[0112] Example 2
[0113] This embodiment provides a method for preparing a silicon dioxide-based composite material, comprising the following steps:
[0114] S1. Add solid sodium silicate with a modulus of 3.45 to 3.55 and process water to a liquefaction tank, and obtain a concentrated sodium silicate solution by high temperature and high pressure liquefaction;
[0115] S2. Add process water to the solution in step S1 and stir sufficiently to obtain a sodium silicate solution having a concentration of 1.90 mol / L and set aside;
[0116] S3. The concentrated sulfuric acid is configured into a 3.50mol / L dilute sulfuric acid solution for standby use;
[0117] S4. The sodium sulfate solution is configured to a mass ratio of 7.5wt% sodium sulfate and set aside;
[0118] S5. Add 1.45wt% ultrafine zinc oxide additive to the solution in step S4, stir for 30min, and set aside;
[0119] S6. Add 8.5m 3 The sodium sulfate solution prepared in step S5 is kept at 90°C, and then 0.3 ml of the sodium silicate dilute solution prepared in step S2 is added. 3 , stir evenly, and control the stirring frequency at 35Hz;
[0120] S7. Add the sodium silicate solution prepared in step S2 and the dilute sulfuric acid solution prepared in step S3 simultaneously for parallel neutralization reaction, and control the pH value of the process at 9.5, wherein the added volume of the sodium silicate solution prepared in step S2 is 6.0m 3 After the sodium silicate is added, the dilute sulfuric acid solution prepared in step S3 is continued to be added dropwise until the end point pH value reaches 3.0 to 4.0, and then the addition is stopped and the mixture is stirred for 30 minutes for aging to obtain a slurry;
[0121] S8. The slurry after maturation in step S7 is subjected to filter pressing and washing to make the conductivity of the washing water of the silica filter cake less than 10000 us / cm, and then dried by air flow, with an inlet temperature of 340°C and an outlet temperature of 105°C, and then air flow crushing is performed with a crushing pressure of 2.0 bar and a classifying wheel speed of 1200 rpm to obtain a silica-based composite material, namely ZS-2.
[0122] The test showed that the silica-based composite material obtained in Example 2 had a water absorption of 15.8 ml / 20 ml, an oil absorption value (castor oil dry pressing) of 75.9 g / 100 g, volatile matter of 2.46% at 105° C., and a maximum transparency of 17% within the refractive index range of 1.330 to 1.460.
[0123] Comparative Example 1
[0124] This comparative example provides a method for preparing a silicon dioxide material, comprising the following steps:
[0125] S1. Add solid sodium silicate with a modulus of 3.45 to 3.55 and process water to a liquefaction tank, and obtain a concentrated sodium silicate solution by high temperature and high pressure liquefaction;
[0126] S2. Add process water to the solution in step S1 and stir sufficiently to obtain a sodium silicate solution having a concentration of 1.0 mol / L and set aside;
[0127] S3. The concentrated sulfuric acid is configured into a 3.0 mol / L dilute sulfuric acid solution for standby use;
[0128] S4. The sodium sulfate solution is configured to a mass ratio of 3.6wt% sodium sulfate for standby use;
[0129] S5. Add 12m 3 The sodium sulfate solution prepared in step S4 is controlled at 78°C, and then 0.2 m sodium silicate solution prepared in step S2 is added. 3 , stir evenly, and control the stirring frequency at 30Hz;
[0130] S6. Add the sodium silicate solution prepared in step S2 and the dilute sulfuric acid solution prepared in step S3 simultaneously for parallel neutralization reaction, and control the pH value of the process at 8.5, wherein the added volume of the sodium silicate solution prepared in step S2 is 4.05m 3 After the sodium silicate is added, the dilute sulfuric acid solution prepared in step S3 is continued to be added dropwise until the end point pH value reaches 3.5, and then the addition is stopped and the mixture is stirred for 30 minutes for aging to obtain a slurry;
[0131] S7. The slurry after maturation in step S6 is subjected to filter pressing and washing to make the conductivity of the washing water of the silica filter cake less than 10000 us / cm, and then dried by air flow, with an inlet temperature of 330°C and an outlet temperature of 105°C, and then air flow crushing is performed, with a crushing pressure of 1.5 bar and a classifying wheel speed of 1000 rpm, to obtain a silica material, namely ZS-3.
[0132] The test showed that the material obtained in Comparative Example 1 had a water absorption of 18.5 ml / 20 ml, an oil absorption value (castor oil dry pressed) of 90.3 g / 100 g, volatile matter of 6.9% at 105° C., and a maximum transparency of 85% within the refractive index range of 1.330 to 1.460.
[0133] Comparative Example 2
[0134] This comparative example provides a method for preparing a silicon dioxide-based composite material, comprising the following steps:
[0135] S1. Add solid sodium silicate with a modulus of 3.45 to 3.55 and process water to a liquefaction tank, and obtain a concentrated sodium silicate solution by high temperature and high pressure liquefaction;
[0136] S2. Add process water to the solution in step S1 and stir sufficiently to obtain a sodium silicate solution having a concentration of 2.0 mol / L and set aside;
[0137] S3. The concentrated sulfuric acid is configured into a 3.5mol / L dilute sulfuric acid solution for standby use;
[0138] S4. The sodium sulfate solution is configured to have a mass ratio of 7.8wt% sodium sulfate and set aside;
[0139] S5. Add 0.28wt% ultrafine zinc oxide additive to the solution of step S4, stir for 30min, and set aside;
[0140] S6. Add 12m 3 The sodium sulfate solution prepared in step S5 is controlled at 85°C, and then 0.13 m sodium silicate solution prepared in step S2 is added. 3 , stir evenly, and control the stirring frequency at 35Hz;
[0141] S7. Add the sodium silicate solution prepared in step S2 and the dilute sulfuric acid solution prepared in step S3 simultaneously for parallel neutralization reaction, and control the pH value of the process at 9.5, wherein the added volume of the sodium silicate solution prepared in step S2 is 5.58m 3 After the sodium silicate is added, the dilute sulfuric acid solution prepared in step S3 is continued to be added dropwise until the end point pH value reaches 3.0 to 4.0, then the addition is stopped and the mixture is stirred for 30 minutes for aging to obtain a slurry;
[0142] S8. The slurry after maturation in step S7 is subjected to filter pressing and washing to make the conductivity of the washing water of the silica filter cake less than 10000 us / cm, and then dried by air flow, with an inlet temperature of 350°C and an outlet temperature of 105°C, and then air flow crushing is performed, with a crushing pressure of 2.5 bar and a classifying wheel speed of 1500 rpm, to obtain a silica-based composite material, namely ZS-4.
[0143] The test showed that the material obtained in Comparative Example 2 had a water absorption of 13.9 ml / 20 ml, an oil absorption value (castor oil dry pressed) of 69 g / 100 g, 3.9% volatile matter at 105° C., and a maximum transparency of 68% within the refractive index range of 1.330 to 1.460.
[0144] Application Examples
[0145] The materials obtained in Examples 1 to 2 and Comparative Examples 1 to 2 were mixed with water, sorbitol, glycerol, hydroxymethyl cellulose, sodium lauryl sulfate, sodium saccharin, flavor, sodium benzoate and ZI-165 in a certain proportion to obtain a toothpaste with a white paste. The specific formula and appearance of the toothpaste are shown in Table 1.
[0146] Among them, ZI-165 is a thickening silica produced by Jinsanjiang (Zhaoqing) Silicon Materials Co., Ltd., with a water absorption of 40-45 ml / 20 g, D 50 The median particle size is 8 to 15 μm, the refractive index is 1.445 to 1.450, and the transparency is ≥ 95%; the following embodiments and comparative examples of the present invention all use the same kind;
[0147] ZS-1, ZS-2, ZS-3, and ZS-4 represent the silica-based composite materials obtained in Examples 1 and 2, the silica material obtained in Comparative Example 1, and the silica-based composite materials obtained in Comparative Example 2, respectively.
[0148] Table 1. Toothpaste formula and appearance effect table prepared by materials of examples and comparative examples
[0149]
[0150]
[0151] Combining Examples 1 to 2 and Table 3, it can be seen that the silica-based composite material prepared by the preparation method of the present invention has low transparency and high hiding power. Among them, the water absorption of the silica-based composite material prepared in Example 1 is 19.2ml / 20ml, the oil absorption value is 95g / 100g, the volatile content at 105°C is 4.7%, and the highest point transparency in the refractive index range of 1.330 to 1.460 is 20%; the water absorption of the silica-based composite material prepared in Example 2 is 15.8ml / 20ml, the oil absorption value is 75.9g / 100g, the volatile content at 105°C is 2.46%, and the highest point transparency in the refractive index range of 1.330 to 1.460 is 17%. The silica-based composite material is added to the toothpaste formula as an abrasive, and the obtained toothpaste has a white paste, is opaque, has high whiteness, and has a smooth surface.
[0152] Compared with Example 1, Comparative Example 1 does not add zinc oxide. Under the same conditions, the prepared silica material has a higher transparency, with the highest transparency reaching 85%. When prepared into toothpaste paste (Application Example 3), it presents a transparent state and a white paste cannot be obtained. It can be seen that the silica material of Comparative Example 1 does not have the performance of low transparency and high hiding power.
[0153] In Comparative Example 2, compared with Example 2, the content of added zinc oxide is 0.28wt%, which exceeds the addition range of 0.3-1.8wt% in the above-mentioned preparation method of the present invention. The highest point transparency of the prepared silica-based composite material is 68%, which has high transparency and poor hiding power. When the silica-based composite material is prepared into a paste (Application Example 4), it presents a translucent state and does not have the characteristics of low transparency and high hiding power.
[0154] Figure 1 Schematic diagram of the synthesis mechanism of the silicon dioxide-based composite material according to the embodiment of the present invention. Figure 1 It can be seen that in the preparation process of the above-mentioned silica-based composite material of the present invention, while the silicate and the acidulant are hydrolyzed to generate silica, the silica polymer is gradually polymerized on the surface of the zinc oxide to form a core-shell structure. When the incident light in the medium reaches the shell, the first refracted light, scattered light, reflected light and the like will occur, and the first refracted light will be used as the incident light of the core-shell layer to generate the second refracted light, scattered light, reflected light and the like at the interface again.
[0155] Figure 2 This is a SEM image of the silicon dioxide-based composite material of Example 2 (scale bar is 5 μm). Figure 2 As shown, the surface of the silica-based composite material obtained by the present invention is a porous uniform material layer, which is a silica polymer, that is, an inorganic high molecular polymer, and the particle size of the silica-based composite material obtained is less than 20 μm. The silica prepared by the precipitation method is polymerized from oligomers to polymers, so the material finally obtained by the present invention shows the porous and uniform characteristics of small particles piled up. This SEM picture shows that the zinc oxide added as a nucleus in the synthesis process makes the silica seed adhere to the surface of the nucleus and start to polymerize, slowly forming oligomers and polymers, and finally wrapping the nucleus to form a core-shell structure with zinc oxide as the inner core and a silica layer as the outer layer.
[0156] In summary, the silica-based composite material obtained by the present invention has a core-shell structure, which can reflect and scatter external light twice. Due to the large difference in the refractive index of the core layer and the shell layer, the reflection and scattered light intensity of the core-shell interface is high, showing a high hiding power, and the obtained silica-based composite material has high hiding power and low transparency by compounding zinc oxide with low transparency and silica polymer. The present invention obtains a silica-based composite material by a one-step precipitation method using zinc oxide and silica composite, which is easy to operate. By further controlling the reaction conditions such as pH, the microstructure of the silica-based composite material can also be regulated to make the structure denser, further enhance the hiding power of the silica-based composite material, and reduce transparency. The silica-based composite material can be used as an abrasive in toothpaste, and the obtained toothpaste is a white paste with excellent whiteness and a smooth appearance.
[0157] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon dioxide-based composite material, characterized in that: The silicon dioxide-based composite material has a core-shell structure, the core layer is zinc oxide, and the shell layer is silicon dioxide polymer; The silica composite material D 50 Particle size <20μm; The preparation method comprises the following steps: A zinc oxide-sulfate slurry containing 0.35-5% by mass of zinc oxide is prepared, and a silicate and an acidulant are added to react, and after aging, the silicon dioxide-based composite material is obtained; The silicate and the acidulant are added in the following manner: after adding the silicate to the zinc oxide-sulfate slurry, Then add the silicate and the acidulant simultaneously, and then continue to add the acidulant; During the simultaneous addition of silicate and acidulant, the pH value of the system is controlled to be 8-10; after the acidulant is continuously added, the pH value of the system is controlled to be 3-4; The silicate is added in the form of a silicate solution; the concentration of the silicate solution is 0.1-2.0 mol / L; the concentration of the acidifier is 1-4 mol / L.
2. The preparation method according to claim 1, characterized in that: The silicate is an alkali metal silicate.
3. The preparation method according to claim 1, characterized in that: The acidulant includes at least one of hydrochloric acid and sulfuric acid.
4. The preparation method according to claim 1, characterized in that: The reaction temperature is 50-90°C; And / or, the aging time is 0.5 to 1 hour.
5. A toothpaste abrasive, characterized in that: The invention comprises a silicon dioxide-based composite material prepared by the preparation method according to any one of claims 1 to 4.
6. A toothpaste, characterized in that: The toothpaste contains the silicon dioxide-based composite material obtained by the preparation method according to any one of claims 1 to 4.
7. The toothpaste according to claim 6, characterized in that The mass fraction of the silicon dioxide-based composite material in the toothpaste is 8-25%.
Citation Information
Patent Citations
Cosmetic composition with increased opacity
CN105636573A
Oral care composition
CN108024912A